Deciding by Argument versus Proving by Miracle: The Myth-History of Talmudic Judaism's Coming of Age - Fish, Menaḥem (Toronto journal of theology, 2017)
Miracles are not only not denied by the rabbis, but are taken and understood by them as divinely intended and significant. They are interpreted literally as heavenly signs and messages exceedingly louder, clearer, and simpler than God's spoken or written word. Divine miracles are by nature neither subtle nor understated. Their sheer unpredictability and jolting abruptness command the attention of those who witness them to the intervening immediacy of their message. And yet, while fully aware and cognizant of their significance and divine import, the rabbis are known to flatly reject miracles in ways they would never reject a verse. The classical example, to which this article is devoted is the widely cited rabbinic legend of the "oven of Akhnai"—a story that, I argue, holds a key to the Talmud's unique theological and religious enterprise. However, to understand it as such requires attending first to another widely cited Talmudic legend, on which, the article argues, the story of the oven builds, and with which it boldly contends—to the equally well-known account of the foundational dispute between the Houses of Hillel and Shammai, and their infamous heavenly resolution.